HUBUNGAN DENSITAS ENERGI DAN ASUPAN CAIRAN DENGAN BERAT JENIS URIN PADA REMAJA - Setyarsih, Liani; Ardiaria, Martha; Fitranti, Deny Yudi (Journal of Nutrition College, 2017)
Background: Hydration status is a condition that describes total body fluid. One of the method of measuring hydration status is urine specific gravity. Energy density of food is the amount energy content of total weight food. Foods with high energy density tend to have a lower water content, which will affect fluid intake. The aim of this research was to know the correlation of energy density and fluid intake with urine specific gravity as one of the markers of hydration status. Method: This was an observational research with cross-sectional study design. The research was conducted in Senior High School 15 Semarang involving 55 subjects by Simple Random Sampling method. Food intake and fluid intake were assessed by 1x24 hours Food Recall. Urine specific gravity measured in laboratory. Body fat percentage measured by BIA (Bioelectrical Impendance Analysis) and physical activity assessed by 1x24 hours record physical activity. Data were analyzed by rank spearman.Result: Median of urine specific gravity men and women was 1,02 g/ml. Mean of energy density in men was 1,8±0,32 kcal/gram, in women was 2,1±0,59 kkal/gram. Mean of fluid intake in men was 2406,4±491,38 ml, in women was 2159,5±648,42ml. There was significant correlation of fluid intake with hydration status (p=0,027). There was no significant correlation of energy density and hydration status (p=0,218). Multivariate analysis showed that 14,6% of hydration status is affected by both fluid intake and energy intake. Conclusion: There was significant correlation of fluid intake with urine specific gravity. There was no significant correlation of energy density and urine specific gravity.